THE PHENOMENON OF «BLACK HOLE» IS IN POLITICAL DISKOURSE - Волков, А. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article opens up, what topology of discourse; such descriptions of space of discourse as surface and lining are selected, the role of intention is also shown in organization of space of political discourse. Attention applies, that every subject possesses a certain mistimed in discoursive space which to congruent space of power. Description is given to such discoursive phenomenon, as a black hole, and also opens up the feature of attitude toward a political subject which is in it.